PENGARUH BEBAN KERJA, WORK LIFE BALANCE DAN DUKUNGAN SOSIAL TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN KOTA KEDIRI - Dendik Irwanto; Brahma Wahyu Kurniawan; Erwin Syahputra (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to determine the influence of workload, work-life balance, and social support on employee performance at the Department of Transportation in Kediri City. The research employed a quantitative descriptive design using survey methods to collect primary data through questionnaires distributed to 40 respondents, selected using purposive sampling from a total population of 175 employees. Secondary data were obtained through literature reviews and institutional documentation. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination (R²) with the help of SPSS version 25. The results showed that workload had no partial effect on employee performance, indicating that high workloads do not necessarily reduce performance when employees possess good time management and adaptability skills. Work-life balance also had no significant effect, suggesting that personal–work balance has not yet become a major determinant of performance in government institutions. In contrast, social support had a positive and significant influence, meaning that emotional and instrumental support from supervisors and coworkers enhances motivation, satisfaction, and productivity. Simultaneously, workload, work-life balance, and social support jointly influence employee performance. The novelty of this research lies in integrating these three variables in the context of public-sector employees, emphasizing the importance of social support and balanced workload management in improving public service quality and human resource performance in government organizations..